(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Objective. Based on assessment of the role of disorders in various links of hemostasis in the pathogenesis of IMTV and ITP and determination of their relation to disease stage, optimize the hemostasiological diagnostic algorithm for the studied pathologies. Materials and methods. The study included 105 patients with IMTV (51 — in the relapse stage, 54 — in the remission stage); 135 patients with ITP (74 — in the relapse stage, 61 — in the remission stage) and 81 conditionally healthy individuals without pathology of the hemostatic system (all subjects were aged 18 to 70 years). The hemostatic system was examined using a HumaClot Junior coagulometer (HC-4127, Germany) and an ALAT-2 “BIOLA” aggregation analyzer (AAS 748, Russia) with reagents from “NPO RENAM, Russia.” Results and discussion. A comprehensive study of the links of the hemostatic system indicates pronounced coagulation disorders, which are one of the main mechanisms in the pathogenesis of IMTV and ITP. IMTV is characterized by activation of the vascular–platelet link and moderate hypercoagulation, whereas ITP is characterized by reduced activity of the vascular–platelet link of hemostasis.